Первое:
x+1=2y
5xy+y^2-16=0
1)
x+1=2y
x=2y-1
2) 5(2y-1)y+y^2-16=0
(10y-5)y+y^2-16=0
10y^2-5y+y^2-16=0
11y^2-5y-16=0
D=25+(4×11×16) = 27
y1 = (5+27)/22 = 33/22 = 3/2 = 1,5
y2 = (5-27)/22 = 1
3) x1 = 2×1,5-1
x1 = 2
x2 = 2×1-1
x2 = 1
Второе:
2х^2-4= -у
3у-х= -14
1)
2х^2-4= -у
у= 4-2х^2
2)
3(4-2х^2)-х= -14
12-6х^2-х= -14
-6х^2-х= -26
-6х^2-х+26=0 |: -
6х^2+х-26= 0
Д= 1^2+(4×6×26) = 1+624 = 25
х1= (-1+25)/12 = 2
х2= (-1-25)/12 = -26/12 = -2 целые 1/6 (дробь)
3) у1 = 4-2(4)
у1 = -4
у2 = 4-2(676/144)
у2 = 4-676/72=4-169/18=72/18-169/18=-97/18=-5 целых 7/18
по мойму правильно
Пошаговое объяснение:
Пошаговое объяснение:
x+1=2y
5xy+y^2-16=0
1)
x+1=2y
x=2y-1
2) 5(2y-1)y+y^2-16=0
(10y-5)y+y^2-16=0
10y^2-5y+y^2-16=0
11y^2-5y-16=0
D=25+(4×11×16) = 27
y1 = (5+27)/22 = 33/22 = 3/2 = 1,5
y2 = (5-27)/22 = 1
3) x1 = 2×1,5-1
x1 = 2
x2 = 2×1-1
x2 = 1
Второе:
2х^2-4= -у
3у-х= -14
1)
2х^2-4= -у
у= 4-2х^2
2)
3(4-2х^2)-х= -14
12-6х^2-х= -14
-6х^2-х= -26
-6х^2-х+26=0 |: -
6х^2+х-26= 0
Д= 1^2+(4×6×26) = 1+624 = 25
х1= (-1+25)/12 = 2
х2= (-1-25)/12 = -26/12 = -2 целые 1/6 (дробь)
3) у1 = 4-2(4)
у1 = -4
у2 = 4-2(676/144)
у2 = 4-676/72=4-169/18=72/18-169/18=-97/18=-5 целых 7/18
по мойму правильно
17,347+4,846+1,154= 17,347+(4,846+1,154)= 17,347+6=23,347
( 12,487+26,789) - 17,589=12,487 + (26,789-17,589)= 12,487+9,2=21,687
15,41-2,93-0,07=15,41 - (2,93+0,07)=15,41 - 3= 12,41